Pengaruh Pandemi COVID-19 Terhadap Kondisi Finansial Rumah Sakit - Amirsyani Ariestotama Ilyas; Theodore Isaac Molandro; Aaisyah Dia Palupi; Moona Fahira; Dian Purbani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The COVID-19 pandemic has put great pressure on hospitals, affecting clinical and non-clinical aspects such as patient care, resource management, and finances. This research analyzes the challenges faced by hospitals through crisis management theory and open systems, with a focus on financial pressures, staff shortages, and digital transformation. The purpose of this writing is to provide insight into hospital strategies in overcoming pandemic challenges, which is expected to improve hospital readiness in the future. Article search was conducted through international databases using the terms PICO and MeSH: P: "COVID-19"; I: "Financial Strategy"; O: "Stability", "Profitability", "Impact". Article selection follows PRISMA guidelines, starting with article identification, duplicate checking, and screening based on inclusion criteria (English articles, original, published 2019-2024) and exclusion (systematic review, literature review, meta-analysis). The COVID-19 pandemic has had a major impact on hospital operations and finances in various countries, including declining revenues, increased operating costs, and pressure on resources. Some hospitals managed to recover through efficiency strategies and government support, while others faced challenges related to regulatory changes and uncertainty. Research shows the importance of adaptive and optimal managerial mitigation strategies to address similar crises in the future. The COVID-19 pandemic has had a major impact on the operations and finances of the global health system, requiring an optimal management strategy. The main challenges facing healthcare providers include financial pressures, changing service patterns, and the importance of effective mitigation strategies to deal with the crisis.